Analysis Of Sustainability Report Disclosure Based On GRI 2021 Standards At BCA Bank In 2023-2024 - Hesty T Salle; Sara Marlyn Paru (UNIVERSITAS PAKUAN, 2025)
This study proposes an analysis of sustainability reporting by Bank BCA, focusing on the Global Reporting Initiative (GRI) standards as the main framework. Sustainability reports that combine financial and non-financial information are crucial for companies to communicate their economic, social and environmental impacts to stakeholders and gain legitimacy. The purpose of this study is to evaluate the extent to which Bank BCA has disclosed sustainability information in accordance with GRI standards, which will provide insights for interested parties regarding the implementation of GRI standards in the Indonesian banking sector. The results show that Bank BCA has implemented sustainability reporting for the 2022–2024 period with high consistency and an upward trend from year to year. In terms of GRI 2 (General Disclosure), BCA achieved fully applied status, thereby strengthening its legitimacy through transparent governance and strategies. GRI 200 (Economic Performance) was in the well applied category with contributions to the creation and distribution of sustainable economic value as a manifestation of the profit dimension. GRI 300 (Environmental Performance) shows a commitment to the planet dimension through recycling initiatives, although there is still room for improvement in the details of waste management, while GRI 400 (Social Performance) is in the well applied to fully applied category with a focus on employee welfare, financial literacy, and social contribution as a manifestation of the people dimension. Overall, the results of this study are in line with the Triple Bottom Line principle and legitimacy theory, and show that the disclosure of sustainability reports not only complies with Law No. 40/2007 and POJK No. 51/2017, but also strengthens employee trust, customer loyalty, and BCA's reputation as a bank committed to sustainability.